2003
DOI: 10.1074/jbc.m303521200
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Metabolism and Energy Homeostasis in Mouse Hearts Overexpressing Dominant Negative α2 Subunit of AMP-activated Protein Kinase

Abstract: AMP-activated protein kinase (AMPK) is an energysensing enzyme that plays a pivotal role in regulating cellular metabolism for sustaining energy homeostasis under stress conditions. Activation of AMPK has been observed in the heart during acute and chronic stresses, but its functional role has not been completely understood because of the lack of effective activators and inhibitors of this kinase in the heart. We generated transgenic mice (TG) with cardiac-specific overexpression of a dominant negative mutant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
217
1
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 207 publications
(236 citation statements)
references
References 34 publications
15
217
1
3
Order By: Relevance
“…A growing number of in-vivo [28][29][30][31] and in-vitro [32] studies have indicated that AMPK activation may directly regulate GLUT-4 expression [11,[28][29][30][31][32][33] and induce a significant increase in glucose uptake [9][10][11][28][29][30][31][32][33][34] in cultured skeletal muscle cells. In cardiomyocytes, hypoxia may increase AMPK-mediated glucose uptake and GLUT-4 translocation [35] , which is not sufficient to increase glucose uptake [36] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing number of in-vivo [28][29][30][31] and in-vitro [32] studies have indicated that AMPK activation may directly regulate GLUT-4 expression [11,[28][29][30][31][32][33] and induce a significant increase in glucose uptake [9][10][11][28][29][30][31][32][33][34] in cultured skeletal muscle cells. In cardiomyocytes, hypoxia may increase AMPK-mediated glucose uptake and GLUT-4 translocation [35] , which is not sufficient to increase glucose uptake [36] .…”
Section: Discussionmentioning
confidence: 99%
“…Its facilitative uptake is dependent on the activity of glucose transporters (GLUT) on the cell surface, in particular, glucose transporter-4 (GLUT-4) [7,8] . The increase in glucose uptake is mainly dependent on GLUT-4 translocation via AMP-activated protein kinase (AMPK) [9][10][11] , phosphatidylinositol-3 kinase (PI3K) [12,13] , etc. The increased glucose uptake provides a substrate for glycolysis and then partly compensates for the energy deficit.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in which hearts are exposed to ischemia in the presence of either no or low levels of fatty acids have suggested that hearts that have a decreased ischemiainduced activation of AMPK result in a decreased recovery of cardiac function. 6,42 However, a recent study in hearts from mice in which AMPKa2 was deleted showed that a decrease in AMPK activation results in no difference in functional recovery following ischemia. 43 We have also recently shown in hearts from AMPK dominate negative mutant of the a2 subunit (DNa2) of mice that if hearts were exposed to either low or high levels of fatty acids there was either no difference in functional recovery, or an actual increase in functional recovery (Folmes et al, unpublished data).…”
Section: Is Ampk Activation Beneficial or Harmful During And Followinmentioning
confidence: 99%
“…Celle-ci est le résultat d'une chute plus rapide d'ATP. La surexpression cardiaque d'une forme dominante négative de l'AMPK inhibe l'activation de l'AMPK, la stimulation de la glycolyse et la production de lactate au cours de l'ischémie et entraîne une aggravation des lésions ischémiques (mort cellulaire) [41,42]. Récemment, l'AMPK a été impliquée dans les effets cardioprotecteurs de l'adiponectine en inhibant l'apoptose des cardiomyocytes [43].…”
Section: Contrôle Du Métabolisme Myocardique Par L'ampkunclassified